The EU vs US corporate R&D intensity gap: Investigating key sectors and firms - Pietro Moncada-Paternò-Castello; Nicola Grassano (European Commission, Joint Research Centre (JRC), 2020)
This paper contributes to the literature on corporate research and development (R&D) intensity decomposition by examining the effects of several parameters on R&D intensity. It draws on a longitudinal company-level micro-dataset, built using four editions of the EU R&D Scoreboard, and confirms the structural nature of the EU R&D intensity gap with the US, which has widened in the last decade. As a novel contribution to the literature, this paper uncovers the differences between the EU and the US by inspecting which sectors and firms are more accountable for the aggregate R&D intensity performance of these two economies. Furthermore, the study shows that a large share of R&D investment by the EU sample is mostly conducted in sectors with medium or low R&D intensity, and that there is a high concentration of R&D in a few sectors and firms. Interestingly, the investigation finds a high heterogeneity in firms' R&D intensity within sectors, indicating the coexistence of firms with different R&D investment strategies and efficiencies. Finally, the study reveals that the EU holds a much lower number of both larger and smaller R&D investors than the USA, in the four high-tech sectors that are key to the aggregate EU R&D intensity gap vis-à-vis the USA.
Keywords: O30; O32; O38; O57; 330; Corporate R&D; R&D intensity decomposition; EU vs US R&D intensity gap; R&D distribution; comparative performance; top world R&D firms